How Muslim Youth Community Brand Sells Merchandise Case: Shift Youth Movement - Kusumawati, Nurrani; Arrahim, Dzikry (School of Business and Management Institut Teknologi Bandung, 2021)
Abstract. Shift is a Muslim youth movement community in Indonesia. As one of the Islamic Brand in Indonesia, Shift starts selling the merchandise to broaden the brand. However, selling the brand's merchandise is not easy work to do. A couple of factors might affect customer purchase intention, such as brand loyalty and brand image. This research aims to find a strategy on how Islamic Brand sell merchandises. This study will discuss several variables, such as brand knowledge, brand satisfaction, brand identification, brand image, brand loyalty, and perceived quality to purchase intention. The data collection uses the questionnaire as the method and analyses it on Partial Least Square Structural Equation Modeling (PLS-SEM). The questionnaires are distributed by online platforms with sample size of 436 respondents who knew about Shift Brand and Shift's Merchandise. The outcomes are brand knowledge, brand satisfaction, brand identification, influence brand image and brand loyalty. Brand loyalty has a positive impact on purchase intention; however, brand image and perceived quality insignificant impact purchase intention. The Shift must develop a strategy to strengthen brand knowledge, brand satisfaction, and brand identification; therefore, it can increase brand loyalty, leading to purchase intention.Keywords: Brand loyalty, brand image, perceived quality, purchase intention, Islamic brand, and partial least square.